New BiCMOS device structures and circuits for low-voltage low-power applications - Yeo, Kiat Seng (2009)
This thesis presents an in depth analysis and the development of a new generation of BiCMOS circuits for present and future VLSI requirements. The work is motivated by the increasing demand in both the speed and low power consumption at low supply voltages. First, two novel inverting circuits and their logic gates are introduced. These circuits employ the BiMOS configuration and are designed for the 23.3V supply voltage regime.